Peran Mal Pelayanan Publik (MPP) Kabupaten Pati dalam Perlindungan Pekerja Migran Indonesia (PMI) - Fitriyono, Junaidul (Universitas Sebelas Maret, 2023)
The Pati Regency Public Service Mall (MPP) is an alternative solution for people who need public services in one place. One service that is widely used is the facilitation of prospective Indonesian Migrant Workers (CPMI) who will work abroad. With the presence of agencies related to the CPMI placement process such as BP2MI, the Manpower Office, the Population and Civil Registration Office, the Office of the Ministry of Religious Affairs and the Immigration Office, it is expected that CPMI will be facilitated in the process of preparing their administrative documents. The employees placed at MPP of Pati Regency are employees who have the capability and knowledge related to the main tasks and functions of each agency, and have interpersonal communication skills in order to provide a comprehensive explanation to CPMI regarding the requirements, stages and procedures for applying for administrative documents. Collaboration, coordination and synergy between agencies is one of the keys to improving the quality of services available at MPP of Pati regency for CPMI. Hopefully, the MPP of Pati regency can provide end-solution service products so that the general public can obtain services in one place.